FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2017-2019 - Christina Audrey Putri (Bina Ekonomi, 2020)
Globalization causes increasingly rapid and intense competition between companies so that companies must continue to improve their performance in order to compete and survive for a long time. The banking sector is no exception. Banking sector stocks are stocks that are chosen by many investors when they are going to invest. Before making investment decisions in the capital market, investors need information about the value of the company or the value of shares which can be obtained by reading and analyzing financial statements. There are many factors that can determine the value of the company, including profitability, company size and dividend policy. This study aims to determine whether profitability, firm size and dividend policy affect firm value. The companies that are the object of this research are banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. Data was collected by purposive sampling based on predetermined criteria. The secondary data obtained were then processed by descriptive statistical methods and multiple linear regression analysis. The results of the study show that profitability variables can be proven to have an effect on firm value, while firm size and dividend policy variables cannot be proven to have an effect on the value of banking companies listed on the Indonesia Stock Exchange in 2017-2019. However, simultaneously, profitability, company size and dividend policy can be proven to have an effect on the value of banking companies listed on the IDX in 2017-2019.